Local Innovation System in Northern Finland – Case Renewable Energy Solutions Pilots in Oulu - Aapaoja, A.; Leviakangas, Pekka (Universitas Indonesia, 2015)
To respond to the dynamics of urban surroundings, enhancing innovativeness in the urban environment has become increasingly important. The major challenge with innovations in urban environment is that many of them do not diffuse easily. The paper identifies the challenges related to urban innovation processes and their scaling-up, using the renewable energy solution pilot project as an example case. This is done by discussing the position and maturity of Renewable Energy Solutions in City Areas (RESCA) in an innovation typology context, and by assessing performed actions aimed at boosting the innovativeness in the case project. Results emphasized the essential role of the local building administration as a proactive stakeholder who started open-mindedly to address old-fashioned, inefficient and dominant practices of the construction industry. Another innovation hot-spot was that market actors needed to collaborate, take steps and present their ideas in order to find, implement and pilot the emerging solutions and innovations.